Desarrollo de una aplicación web para la enseñanza de la asignatura de matemáticas para niños de tercer año de Educación Básica en la Unidad Educativa Intercultural Bilingüe Huayna Capac utilizando la metodología kanban. - Bastidas Racines, Kevin Alejandro (2022)
Learning mathematics is fundamental in the area of education and in daily life, especially for children who require the use of basic and elementary operations to develop activities of daily life. In the teaching process there are concerns on the part of the professionals who teach these subjects, by virtue of the fact that they require the application of pedagogical and technological resources to strengthen their application and a better understanding of the contents of the subject and the achievement of the results. Learning. With the development of the use of technology that was strengthened from the Covid-19 pandemic, where technological tools were implemented to support the teaching-learning processes, which allowed communication between teachers and students and the strengthening of educational processes. . By virtue of the changes established in the educational processes for children in the area of mathematics, the development of a Web Application for the teaching of mathematics in children from 8 to 9 years of age is considered important. For the development of the system, the KANBAN methodology is applied due to its easy implementation, management, optimization and visualization of the work process. For the construction of the system, the Python programming language is applied with Django and the database connection is established through SQlite3, as a result an application with easy access, reliability and a user-friendly graphical interface is obtained.